Early Withdrawals of Pension Funds Due to COVID-19 Effect in Peru - Chambi Condori, Pedro Pablo; Chambi Vásquez, Miriam; Galván Rodríguez, Sara (Sociedad y Economía, 2024)
The aim of the study is to analyze the contexts in which early withdrawals of funds from the private pension system were executed in the period 2020 to 2022 and which have had a negative impact on the amounts received by fund holders. For this purpose, we used the database of the registry of members of the private pension system of the Peruvian Superintendency of Banking and Insurance, as well as the time series statistics of withdrawals of the four types of funds of the private pension system, the statistics of the share value of the funds and the time series of the behavior of the global capital markets. It is concluded that early withdrawals of pension funds were executed in bearish periods in the capital markets, which affected the funds’ quota value and the withdrawals of diminished amounts received by the fund holders.